Evidence brief: Co-designing sustainable approaches to the citizen co-led design, execution and oversight of health-system transformations in Canada - Gauvin, François-Pierre; Moat, KA; Lavis, JN (My University, 2023)
A synthesis of what is known, based on the best available global and local research evidence about the problem(s) related to co-designing sustainable approaches to the citizen co-led design, execution and oversight of health-system transformations in Canada, elements of a potentially comprehensive approach for addressing it, and key implementation considerations. This evidence brief was prepared to inform a stakeholder dialogue.
Keywords: sustainable approaches; citizen; design; execution; oversight; health-system transformations; Canada